Transformer le lait local en Afrique de l'Ouest Procédés et clés du développement des minilaiteries - Brouti, Cécile (éditions Quae, 2021)
Milk production and marketing in West Africa is an integral part of the economy and way of life of rural herder and agropastoralist families. They represent a significant socio-economic and environmental challenge for the region. Despite the dynamism of the local milk sector, marked by an increase in the number of mini-dairies, the current supply remains insufficient to meet the increase in demand, which is growing faster than production, particularly in the cities. Family farms remain poorly connected to the market and have little incentive to increase their sales. They also face constraints in organising collection, as well as management and marketing difficulties. This book is intended for managers, promoters and advisers of mini-dairies. It provides information on the processing of dairy products and presents the key points for the development of these structures. It provides information on the processing of dairy products and presents the key points for the development of these structures. In a didactic manner, based on GRET's experience, and combining theory and practice, it provides the elements of understanding necessary for the proper conduct of this activity. This guide is completed by a series of sheets summarising the processing stages of the main dairy products manufactured in West Africa.